Molecular mechanism of the anti-diabetic activity of an identified oligosaccharide from Rosa canina - Gholamreza Bahrami; Seyed Shahram Miraghaee; Bahar Mohammadi; Mohammad Taher Bahrami; Gholamreza Taheripak; Samira Keshavarzi; Atefeh Babaei; Soraya Sajadimajd; Razieh Hatami (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: Because of the high prevalence, diabetes is considered a global health threat. Hence, the need for effective, cheap, and comfortable therapies are highly felt. In previous study, a novel oligosaccharide with strong anti-diabetic activity in the crude extract of Rosa canina fruits, from the rosacea family, was identified. The present study was designed to ensure its efficacy using in vivo and in vitro studies. Experimental approach: Crude extract and its purified oligosaccharide were prepared from corresponding herb. Adult male Wistar rats were randomly divided into four groups of 10 each, as follows: group 1, healthy control rats given only sterile normal saline; group 2, diabetic control rats received sterile normal saline; group 3, diabetic rats treated with crude extract of Rosa canina (40% w/v) by oral gavage for 8 weeks; group 4, diabetic rats treated with purified oligosaccharide of Rosa canina (2 mg/kg) by oral gavage for 8 weeks. After treatment, body weight, fasting blood glucose, serum insulin levels and islet beta-cell repair and proliferation were investigated. The possible cytoprotective action of oligosaccharide was evaluated in vitro. The effect of oligosaccharide on apoptosis and insulin secretion in cell culture media were examined. Real-time PCR was used to determine the expression level of some glucose metabolism-related regulator genes. Findings / Results: In the animal model of diabetes, the insulin levels were increased significantly due to the regeneration of beta-cells in the islands of langerhans by the purified oligosaccharide. In vitro cell apoptosis examination showed that high concentration of oligosaccharide increased cell death, while at low concentration protected cells from streptozotocin-induced apoptosis. Molecular study showed that the expression of Ins1 and Pdx1 insulin production genes were increased, leading to increased expression of insulin-dependent genes such as Gck and Ptp1b. On the other hand, the expression of the Slc2a2 gene, which is related to the glucose transporter 2, was significantly reduced due to insulin concentrations. Conclusion and implications: The purified oligosaccharide from Rosa canina was a reliable anti-diabetic agent, which acted by increasing insulin production in beta-cells of the islands of Langerhans.